(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Microfinancing allows those with low incomes or no access to traditional banking services toreceive small loans. When it comes to starting or expanding a small business, many people worry abouttheir ability to get a loan, but thanks to microfinance, they may do so in a safe, responsiblemanner.Governments play an active role in microfinance setting policy for the microfinance industry(most frequently vis-à-vis interest rates), providing lump sum grants to NGOs or other microfinanceinstitutions (MFIs), or lending directly to the poor.Women’s access to microfinance as a tool to alleviatepoverty and boost their economic standing has gained widespread attention. In the last five years, therehas been growing scepticism that microcredit is the best way to help the poor, and especially women,improve their financial standing. It is commonly held by development professionals in India and otherdeveloping nations that the state and public institutions have failed to meet the . financing as a solutionfor the poor.